Estudo do comportamento e sistematização do projeto de ligações rígidas entre perfis I com almas coplanares - Gilson Queiroz (1992)
Two types of rigid connections for I sections with coplanar webs are analysed: completely welded and bolted with extender end plate. Their ultimate strengths are determined for stiffened and unstiffened columns. The determined for stiffened and unstiffened columns. The connection stiffnes is estimated in tlhe elastic zone and a joint model is proposed where the connection behavior can be represented by springs. A computer program for automatic design of the two types of connections - where colum stiffners are used only if necessary - is developed. The imput of the program are the factored internal forces in the connected members, as well as the dimensions of the sections. After the connection design, the same program provides the spring constants to be used in the proposed joint model. Two application examples are presented, showing the influence of the connection stiffnes in the structural response